lÄda á¹¢iyÄghah Manhaj al-DirÄsah LishuÊ»bati al-Lughati al Arabiyyati wa ÄdÄbihÄ bi al-JÄmiÄt: Muqtariá¸¥un li-Maná¸¥aj al-DirÄsati al- QÄimi âalÄ alKafÄ-Äti á¹¬abqan li-Mutaá¹allibÄt al âAá¹£r - AfandÃ„Â«, AÃ¡Â¸Â¥mad Fuad (Al-Jamiah Research Centre, 2004)
The Globalization and Industrialization era demand a high quality graduate in relevant competen with peoples demand, including working world. In order to answer the challenge, a curriculum formulation for Arabic language and literature in University is necessary which is oriented to increasing a quality of graduate and based on the result of peoples demand analysis, beside main topics of Arabic study analysis. This curriculum should be flexible which is possible to elaborate some competence options based on people demand and interest / talent of student. It is consists of (1) Scientific Materials (linguistic, literature and culture of Arab), (2) Language skills (listening, speaking, readings, writing), (3) Main expertise / profession ( 4) Support expertise / profession and (5) Religion and social. Â Â